In between international orders - An era of instability: The need for a reform agenda and a new narrative - Michael Reiterer (The Vienna Institute for International Economic Studies (wiiw), 2024)
While Russia's war of aggression on Ukraine is shaking the liberal international order, the Global South is using the occasion to demand overdue reforms and complaining about the neglect of its acute structural problems. Alternative organisations, such as BRICS, the Shanghai Cooperation Organisation and various new development banks, are stepping out of the shadows. At the same time, efforts to achieve more economic security by making supply, production and value chains more resilient are also offering a chance for change - if well steered - to prevent industrial policy at home from turning into protectionism abroad.
Keywords: J02; F13; F53; F55; 330; BRICS; Global South; Economic Security; Indo-Pacific; managing change